2018
DOI: 10.18201/ijisae.2018644778
|View full text |Cite
|
Sign up to set email alerts
|

Human Gender Prediction on Facial Mobil Images using Convolutional Neural Networks

Abstract: The interest in automatic gender classification has increased rapidly, especially with the growth of online social networking platforms, social media applications, and commercial applications. Most of the images shared on these platforms are taken by mobile phone with different expressions, different angles and low resolution. In recent years, convolutional neural networks have become the most powerful method for image classification. Many researchers have shown that convolutional neural networks can achieve b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Chan et al [21] conducted an experiment comparing six shortest path algorithms: Dijkstra's, Symmetrical Dijkstra's, A*, Bellman-Ford, Floyd-Warshall, and Genetic Algorithm. They concluded that the Bellman algorithm was superior among other algorithms as it produced the optimal solution in a short time.…”
Section: Lacorte and Chavezmentioning
confidence: 99%
“…Chan et al [21] conducted an experiment comparing six shortest path algorithms: Dijkstra's, Symmetrical Dijkstra's, A*, Bellman-Ford, Floyd-Warshall, and Genetic Algorithm. They concluded that the Bellman algorithm was superior among other algorithms as it produced the optimal solution in a short time.…”
Section: Lacorte and Chavezmentioning
confidence: 99%
“…Gender prediction models are widely used across different domains such as advertising, security and human–computer interaction. Similar to [ 2 , 6 , 19 , 26 , 36 , 37 , 58 , 77 ], we focus on gender prediction from facial images. Some of these works [ 2 , 19 , 26 , 36 , 58 ] proposed the use of CNN models to predict the gender.…”
Section: Related Workmentioning
confidence: 99%
“…Similar to [ 2 , 6 , 19 , 26 , 36 , 37 , 58 , 77 ], we focus on gender prediction from facial images. Some of these works [ 2 , 19 , 26 , 36 , 58 ] proposed the use of CNN models to predict the gender. Abirami et al [ 2 ] used a CNN model to jointly predict the gender and the age of a person from facial images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…GF addition also reduces the crack width and negative temperature effects [12,13]. Data based prediction models including ANN, Multiple Linear Regression (MLR) are widely used in various engineering applications [14][15][16][17]. These models can give further information for a better understanding of the material properties [18].…”
Section: Introductionmentioning
confidence: 99%